Women’s struggle against patriarchal practice as portrayed in Miriam Toews Women Talking - Cindy Maimuna Hajir Hajir; Linusia Marsih (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study aims to examine the patriarchal practices depicted in Toews, Women Talking and the forms of women's struggle against patriarchal practices. In discussing the problems stated in this thesis, The theories related to patriarchy and feminism are applied. The patriarchy theory used is Wallby's theory, and the feminism theory used is Kate Millet's radical feminism. These theories are used as the writer’s guideline in reveal and describing patriarchal practices and forms of women's struggles in the novel. This research is a qualitative descriptive research with a feminist literary criticism approach. The feminist criticism approach is used because this research focuses on women oppression due to patriarchal practice in the novel. The data of this research is narrative dialogues that reflects forms of patriarchal practices and women's struggles against patriarchal practices. The results of the analysis show that there are three forms of patriarchal practices depicted in the novel namely, male power, and power abuse, limited access of women in education, and oppression on women. To fight against the form of patriarchal practices, the female characters in the novel fight by building self-awareness, becoming androgynous, and reversing the patriarchal system that reflects the radical feminism sparked by Kate Millet. The findings of this study is that the root of the oppression on women is due to patriarchal practices that still occur in society so to fight and be free from patriarchal practice women must have the courage to empower their rights and obtain their freedom, and they must also dare to speak to demand the oppression.